2021
DOI: 10.1021/acsomega.1c03805
|View full text |Cite
|
Sign up to set email alerts
|

Conductive Geopolymers as Low-Cost Electrode Materials for Microbial Fuel Cells

Abstract: Geopolymer (GP) inorganic binders have a superior acid resistance compared to conventional cement (e.g., Portland cement, PC) binders, have better microbial compatibility, and are suitable for introducing electrically conductive additives to improve electron and ion transfer properties. In this study, GP–graphite (GPG) composites and PC–graphite (PCG) composites with a graphite content of 1–10 vol % were prepared and characterized. The electrical conductivity percolation threshold of the GPG and PCG composites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Glass fiber mats of different thicknesses were tested in MFCs together with J‐cloth and CEM. In comparison, the 1.0 mm thick glass fiber mats and J‐cloth showed similar maximum power densities (790 mW m −2 ) and performed significantly better than the CEM 84. The Coulombic efficiency (CE) of MFCs with 1.0 mm thick non‐biodegradable glass fiber mats (81 %) is significantly higher than that of J‐cloth.…”
Section: Electrode and Membrane Materials For Mesmentioning
confidence: 96%
See 1 more Smart Citation
“…Glass fiber mats of different thicknesses were tested in MFCs together with J‐cloth and CEM. In comparison, the 1.0 mm thick glass fiber mats and J‐cloth showed similar maximum power densities (790 mW m −2 ) and performed significantly better than the CEM 84. The Coulombic efficiency (CE) of MFCs with 1.0 mm thick non‐biodegradable glass fiber mats (81 %) is significantly higher than that of J‐cloth.…”
Section: Electrode and Membrane Materials For Mesmentioning
confidence: 96%
“…Metal as anode electrode is used due to its conductivity and electron flow [84]. Metals have low interfacial impedance and low internal resistance compared to carbon-based materials [85].…”
Section: Electrode Materials For Mesmentioning
confidence: 99%
“…In a previous study, we demonstrated that the addition of graphite to GP‐mortar can lead to electrically conductive GP‐electrodes [26] . It was assumed that a graphite network was formed inside the GP, which allowed the application of the modified GP as electrode.…”
Section: Introductionmentioning
confidence: 99%
“…Geopolymers have attracted the attention of researchers recently and have demonstrated much better compatibility with carbon-based (nano)­materials in preparing functional cementitious composites than Portland cement . Depending on the kind of raw material selection and processing conditions, geopolymer binders exhibit an extensive variety of properties and characteristics, including low shrinkage, high compressive strength, fast or slow setting, fire resistance, increased acid resistance in comparison to Portland cement, and low thermal conductivity. , Most of the CNT-geopolymer research has focused on physically dispersing CNT into alkaline activators through ultrasonication and/or the use of surfactants and superplasticizers.…”
Section: Introductionmentioning
confidence: 99%